Pengaruh Gaya Kepemimpinan dan Lingkungan Kerja terhadap Kinerja Karyawan UMKM di Kabupaten Boyolali - Ardian Irawandanu; Mirzam Arqy Ahmadi (PPIMAN Pusat Publikasi Ilmu Manajemen, 2024)
In the era of globalization, the success of a company depends on the ability of human resources to adapt to an increasingly open and diverse work environment, with the main challenges for HR related to cultural diversity and leadership dynamics. This study examines the influence of leadership style and work environment on the performance of MSME employees in Boyolali Regency, filling the gap from previous studies that produced different findings. Using a quantitative approach, data were collected through a survey of 152 employees and analyzed using the SEM PLS method. The results showed that both variables had a significant effect on performance. Although validity and reliability were met, this study was limited to the scope of local MSMEs without considering external factors. These findings emphasize the importance of leadership and work environment in improving the performance of MSME employees.